Reduction of sulfur in fuel oil using Fe2O3 hybrid nanoadsorbent by solvent deasphalting and optimization of operational parameters with CCD - Mohammadreza Malek; Mohammad Samipourgiri; Alimorad Rashidi; Nasrolah Majidian (Scientific Reports, 2024)
Abstract The present study investigated and tested the effect of adding three types of nanoadsorbents (multi-walled carbon nanotubes (MWCNT)) in pure form, multi-walled carbon nanotubes with Fe2O3 particles (MWCNT-Fe2O3) hybrid, and Silanated-Fe2O3 hybrid to heavy fuel oil to reduce sulfur using a deasphalting process with solvent. First, all three types of nanoadsorbents were synthesized. Then, the Central Composite Design (CCD) method was used to identify the parameters effective in deasphalting, such as the type of nanoadsorbent, the weight percentage of nanoadsorbent, and the solvent-to-fuel ratio, and to obtain their optimal values. Based on the optimization result, under laboratory temperature and pressure conditions, the highest percentage of sulfur reduction in deasphalted fuel (DAO) was obtained by adding 2.5% by weight of silanated-Fe2O3 nano-adsorbent and with a solvent-to-fuel ratio of 7.7 (The weight percentage of sulfur in DAO decreased from 3.5% by weight to 2.46%, indicating a decrease of 30%). Additionally, by increasing the temperature to 70 °C, in optimal conditions, the results revealed that the remaining sulfur percentage in DAO decreased to 2.13% by weight, indicating a decrease of 40%. Synthesized nanoadsorbents and asphaltene particles adsorbed on the surfaces of nanoadsorbents were evaluated by XRD, FTIR, FESEM, and TEM techniques.